Mutation analysis of "Endoglin" and "Activin receptor-like kinase" genes in German patients with hereditary hemorrhagic telangiectasia and the value of rapid genotyping using an allele-specific PCR-technique - Haneen Sadick; Johanna Hage; Ulrich Goessler; Jens Stern-Straeter; Frank Riedel; Karl Hoermann; Peter Bugert (BMC, 2009)
Abstract Background Hereditary hemorrhagic telangiectasia (HHT), also known as Rendu-Osler-Weber syndrome, is an autosomal dominant disorder which is clinically characterised by recurrent epistaxis, mucocutaneous telangiectasia and visceral arteriovenous malformations. Genetic linkage studies identified two genes primarily related to HHT: endoglin (ENG) on chromosome 9q33-34 and activin receptor-like kinase1 (ACVRL1) on chromosome 12q13. We have screened a total of 41 unselected German patients with the suspected diagnosis of HHT. Mutation analysis for the ENG and ACVRL1 genes in all patients was performed by PCR amplification. Sequences were then compared to the HHT database http://www.hhtmutation.org sequences of the ENG mRNA (accession no. BC014271.2) and the ACVRL1 mRNA (accession no. NM000020.1). Results We identified 15 different mutations in 18 cases by direct sequencing. Among these mutations, one novel ENG mutation could be detected which has not yet been described in the literature before. The genotype-phenotype correlation was consistent with a higher frequency of pulmonary arteriovenous malformations in patients with ENG mutations than in patients with ACVRL1 mutations in our collective. Conclusion For rapid genotyping of mutations and SNPs (single nucleotide polymorphisms) in ENG and ACVRL1, allele-specific PCR methods with sequence-specific primers (PCR-SSP) were established and their value analysed.